Development Model of Tourism Communication and Creative Economy Based on Local Culture in East Sumba - Sari, Wulan Purnama; Pandrianto, Nigar; Sukendro, Gregorius Genep; Azeharie, Suzy; Irena, Lydia (Jurnal Komunikasi, 2023)
As something unique, local culture can be utilized in various fields, one of which is tourism. The development of the tourism industry is characterized by several things, for example there is an increase in community participation to advance the local tourism industry, and the use of the creative economy. This research itself was carried out by looking at the potential that Indonesia has in the tourism and creative economy sectors which still have great potential to be developed further while still supporting the preservation of Indonesia's local culture. The research was carried out at a location in East Sumba, because it has a natural attraction for tourism which is already worldwide, but its development so far has not been optimal. Apart from having natural potential for tourism development, Sumba also has local culture and creative economy products, such as woven fabrics. This research was conducted with the main aim of producing a model for the development of tourism and creative economy based on local culture. This research itself will focus on the use of local culture in the tourism sector and the creative economy in tourism communication studies. The research was conducted using a qualitative approach and case study method. Data was obtained through FGD and interviews with resource persons. Based on the research results, it can be concluded that East Sumba has potential in terms of tourism development, the potential is in the form of natural resources, creative economic products, local culture and infrastructure suggestions. Developing this potential must receive support from the government in the form of development and policy making that favors local communities. Apart from that, tourism development also requires the development of human resources, which therefore requires collaboration between the government and local communities.